The inhibition effects of chlorogenic acid on the formation of colored oxidation products of (−)-epigallocatechin gallate under enzymatic oxidation. (15th August 2023) - Cui, Yuqing; Han, Zisheng; Lian, Li; Zhang, Liang
Highlights: Identifying critical colored oxidation products of (-)-epigallocatechin gallate. Oolongtheanin 3-O′-gallate degraded product quinone was critical colored product. Chlorogenic acid significantly inhibited the color of EGCG oxidation mixture. Abstract: Untargeted Liquid chromatography tandem mass spectrometry (LC-MS) based metabolomics in combination with UV–visible and colorimeter was applied in identifying critical colored enzymatically oxidized products of (-)-epigallocatechin gallate (EGCG). Pearson correlation coefficient analysis between marker compounds and a * value was conducted, and then a series of colored oxidation products were targeted and subsequently identified by diode array detection and mass fragmentation ions. The quinone of oolongtheanin 3- O ′-gallate degraded product with quasi-molecular mass ion at m / z 711 was identified as a critical colored oxidation product of single EGCG. To explore the effect of chlorogenic acid on the formation of colored EGCG enzymatic oxidation products, the variation of oxidation products on the oolongtheanin pathway was semi-quantitatively determined. The result showed chlorogenic acid significantly inhibited the formation of colored oxidation products, thus lightened the color of EGCG oxidation mixture. The addition of chlorogenic acid influences the process of tea polyphenols' enzymatic oxidation.